Detecting tuberculosis in pregnant and postpartum women in Eswatini - Munyaradzi Pasipamire; Edward Broughton; Mandzisi Mkhontfo; Gugu Maphalala; Batsabile Simelane-Vilane; Samson Haumba (AOSIS, 2020)
Background: Tuberculosis diagnosis in pregnancy is complex because tuberculosis symptoms are often masked by physiological symptoms of pregnancy. Untreated tuberculosis in pregnant and postpartum women may lead to maternal morbidity and low birth weight. Tuberculosis in HIV-positive pregnant women increases the risk of maternal and infant mortality. Objective: This study aimed to determine tuberculosis prevalence stratified by HIV status and identify screening algorithms that maximise detection of active tuberculosis among pregnant and postpartum women in Eswatini. Methods: Women were enrolled at antenatal and postnatal clinics in Eswatini for tuberculosis screening and diagnostic investigations from 01 April to 30 November 2015 in a cross-sectional study. Sputum samples were collected from all participants for tuberculosis diagnostic tests (smear microscopy, GeneXpert, MGIT culture). Blood and urine samples were collected from HIV-positive women for cluster-of-differentiation-4 cell count, interferon gamma release assay and tuberculosis lateral flow urine lipoarabinomannan tests. Results: We enrolled 990 women; 52% were pregnant and 47% were HIV-positive. The prevalence of tuberculosis among HIV-positive pregnant women was 5% (95% confidence interval [CI]: 2-7) and among postpartum women it was 1% (95%CI: -1-3). Tuberculosis prevalence was 2% (95%CI: 0-3) in HIV-negative pregnant women and 1% (95%CI: -1-2) in HIV-negative postpartum women. The national tuberculosis symptom screening tool failed to identify women who tested tuberculosis-culture positive. Conclusion: Routine tuberculosis symptom screening alone is insufficient to rule out tuberculosis in pregnant and postpartum women. Only sputum culture maximised the detection of tuberculosis, indicating a need to balance access and cost in developing countries.